Vegetation development in post-gold mining revegetation area in Minahasa, North Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Lestari KG, Budi SW, Suryaningtyas DT, Yudhiman E. 2022. Vegetation development in post-gold mining revegetation area in Minahasa, North Sulawesi, Indonesia. Biodiversitas 23: 3224-3233. Gold mining activities in Indonesia, in many areas, have a negative impact on the environment. Activities that can improve the quality of post-mining land include revegetation activities, which are included in post-mining land reclamation activities. The purpose of this study was to analyze the development of vegetation in post-gold mining revegetation areas. Vegetation data were collected using the plotted line method (natural forest) and the Systematic Sampling method with Random Start (revegetation area). The analysis found that the vegetation structure in the post-gold mining revegetation area aged 3 to 10 years has complete vegetation levels (saplings, saplings, poles, and trees). Compared to natural forest, which only includes 30 tree species and 7 herbaceous, this revegetation region has a greater diversity of species, with 66 tree species and 16 herbaceous. The longer the age of revegetation is not followed by an increase in species and an increase in the value of the species diversity index. However, it is still better than the revegetation at a young age and is closer to the condition of a natural forest. The revegetation area aged 8 and 7 years has a higher number of species than natural forests and other revegetation areas.